(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the issue of correctly planning physical loads during the training process of 16-17-year-old judo athletes. The optimal distribution of loads during training contributes to the physical development and improvement of athletes’ results. The study investigates methods for determining loads and their effectiveness.